Quota and Voice Reform : Elements of a Possible Approach, Statistical Appendices I and II, Request for Additional Simulations, Statement by the Managing Director, and Summing Up of the Board Meeting. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
NULL.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet